Development of Contextual Based Narrative Writing Module for Grade X Student of SMK - Putri Wulandari; Awani Manurung; Salamuddin Selian (AKSIS: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
This study aims to describe the development of modules, validation of module development, and improve the learning outcomes of contextual based narrative writing. This research was conducted in class X SMK Ar-Rahman, Medan.The method used is a research and development method. Researchers use expert/expert validation and students to produce products and test the effectiveness of the product.The results obtained from this study: first, the development of contextual writing narrative essay writing modules is needed and appropriate by both teachers and students in the learning process.Second, the results of the validation carried out by experts / experts on the contextual writing narrative essay writing module are very good and worthy of being used as modules with an average percentage rating of 86% and are in the category of "very good", the results of individual trials obtained an average value an average of 87%, the results of small group trials obtained an average value of 88%, and the results of limited field trials obtained an average value of 92%.Third, the development of contextual writing narrative essay writing modules can improve student learning outcomes. This can be seen from the average pretest score of 61, while the average posttest score of 88 with an effectiveness level of 88% is in the "very good" category. Keywords: development, module, writting narrative essays, contextual Abstrak Penelitian ini bertujuan untuk mendeskripsikan pengembangan modul, validasi pengembangan modul, dan meningkatkan hasil belajar menulis karangan narasi berbasis kontekstual. Penelitian ini dilakukan di kelas X SMK Ar-Rahman, Medan. Metode yang digunakan adalah metode penelitian dan pengembangan. Peneliti menggunakan validasi pakar/ahli dan siswa untuk menghasilkan produk serta menguji keefektifan produk. Hasil yang diperoleh dari penelitian ini: pertama, pengembangan modul menulis karangan narasi berbasis kontekstual sangat dibutuhkan dan sesuai oleh guru maupun siswa dalam proses pembelajaran. Kedua, hasil validasi yang dilakukan oleh pakar/ahli terhadap modul menulis karangan narasi berbasis kontekstual bernilai sangat baik dan layak digunakan sebagai modul dengan presentase penilaian rata-rata sebesar 86% dan berada pada kategori “sangat baik”, hasil uji coba perorangan diperoleh nilai rata-rata 87%, hasil uji coba kelompok kecil diperoleh nilai rata-rata 88%, dan hasil uji coba lapangan terbatas diperoleh nilai rata-rata 92%. Ketiga, pengembangan modul menulis karangan narasi berbasis kontekstual dinyatakan dapat meningkatkan hasil belajar siswa. Hal ini dapat dilihat dari nilai rata-rata pretest sebesar 61, sedangkan nilai rata-rata posttest sebesar 88 dengan tingkat efektivitas 88% berada pada kategori “sangat baik”. Kata kunci: pengembangan, modul, menulis karangan narasi, kontekstual